2021
DOI: 10.3389/fphar.2021.645130
|View full text |Cite
|
Sign up to set email alerts
|

Exposure-Response Modeling to Support Dosing Selection for Phase IIb Development of Kukoamine B in Sepsis Patients

Abstract: Aim: Kukoamine B, a small molecule compound, is being developed for the treatment of sepsis in a Phase II clinical trial. The objective of this study was to optimize dosing selection for a Phase IIb clinical trial using an exposure-response model.Methods: Data of 34 sepsis patients from a Phase IIa clinical trial were used in the model: 10 sepsis patients from the placebo group and a total of 24 sepsis patients from the 0.06 mg/kg, 0.12 mg/kg, and 0.24 mg/kg drug groups. Exposure-response relationship was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The results of our study showed that the multiple intravenous infusion of KB in healthy volunteers for the dose range of 0.06-0.24 mg/kg was safe. These findings are comparable to those of Wang et al, who reported no major AEs associated with a 0.24 mg/kg dose regimen in patients with sepsis and so recommended it for further clinical trials [17]. Additionally, hypertriglyceridemia was the most frequently reported AE in both the KB group (4, 22.22%) and the placebo group (2, 33.33%) during the trial.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of our study showed that the multiple intravenous infusion of KB in healthy volunteers for the dose range of 0.06-0.24 mg/kg was safe. These findings are comparable to those of Wang et al, who reported no major AEs associated with a 0.24 mg/kg dose regimen in patients with sepsis and so recommended it for further clinical trials [17]. Additionally, hypertriglyceridemia was the most frequently reported AE in both the KB group (4, 22.22%) and the placebo group (2, 33.33%) during the trial.…”
Section: Discussionsupporting
confidence: 85%
“…Hence, they are not particularly efficient at combating sepsis as both aforementioned molecules are usually involved during sepsis. Therefore, LPS and CpG DNA could be used as co-targets for sepsis drugs in the development of novel sepsis therapies such as kukoamine B (KB) [17].…”
Section: Introductionmentioning
confidence: 99%
“…The predicted concentrations vs time (0–8 h) on the two dosing regimens are plotted in Figure 6. The exposure (AUC) of the fixed dose was approximately the target AUC 1500 ng*h/mL 21 …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 13 , kukoamine B (CAS: 164991-67-7), as a novel dual inhibitor of LPS and CpG DNA, regulates the downstream signal pathway by directly binding and neutralizing LPS and CpG DNA, thus significantly inhibiting the inflammatory response in LPS-induced septic mice [ 79 ]. Wang et al [ 80 ] used an exposure-response model to optimize dose selection in phase IIb clinical trials and recommended a 0.24 mg/kg regimen. A randomized, double-masked, placebo-controlled, multi-dose phase I study also demonstrated that single and multiple intravenous infusions of 0.06–0.24 mg/kg were safe and tolerable in healthy volunteers [ 81 ].…”
Section: Alkaloid Compoundsmentioning
confidence: 99%